Updating methods of teaching economic disciplines in the conditions of economic education modification - Svetlana Kadirbechivna Yeshugova; Galina Vladimirovna Kadakoeva (Вестник Майкопского государственного технологического университета)
The systemic transformation of the Russian society in modern market conditions assigns a special role to economic sciences, which form the economic outlook of citizens. The continuous improvement of the quality of economic education in general and methods of teaching economic disciplines, in particular, seems to be undeniably relevant. In the context of a two-level education system in the Russian Federation, the theoretical unpreparedness and dogmatic practical orientation of graduates of economic training areas is completely unacceptable. In this aspect the role of a teacher in the educational process and the use of modern educational technologies and their constant improvement are especially significant. The above mentioned circumstances determine the relevance of the topic of the study. The research substantiates the need for continuous improvement of an integrated approach to teaching economic disciplines, systematizes the experience of teaching economic disciplines in Russian higher educational institutions. The article proposes a new understanding of the process of improving teaching methods of economic disciplines and improving the quality of economic knowledge of students, the author’s list of methods of teaching economic disciplines is given. The following research methods have been used: a formalized method for parsing and analyzing methodological developments, systematization and data synthesis.